Interrogation of ERG gene rearrangements in prostate cancer identifies a prognostic 10‐gene signature with relevant implication to patients' clinical outcome. (5th September 2013) - Bismar, Tarek A.; Alshalalfa, Mohammed; Petersen, Lars F.; Teng, Liang Hong; Gerke, Travis; Bakkar, Ashraf; Al‐Mami, Amal; Liu, Shuhong; Dolph, Michael; Mucci, Lorelei A.; Alhajj, Reda
Abstract : Objectives: ERG ‐gene rearrangement defines a distinct molecular subtype of PCA with potential biological and clinical implications. To identify a molecular signature reflective of the downstream effects of ERG‐ mediated transcriptional regulation with prognostic implication in patients with prostate cancer (PCA). Material and Methods: We used a singular value decomposition (SVD) bioinformatics approach to re‐analyse gene expression data previously generated from 46 prostate tumours, and identified an ERG‐ like gene signature. The signature was validated on several patient cohorts and individual genes were correlated to ERG expression and PCA progression. Results: An ERG ‐like 10‐gene signature was identified and validated in PCA cohorts of the physician health study (p115) ( n = 110) in addition to three independent public datasets, and was significantly associated with disease progression, biochemical recurrence and PCA‐specific mortality. Patients with the ERG‐ like signature were significantly associated with disease recurrence on univariate (hazard ratio [HR] 2.6; 95% confidence interval [CI]:1.3–5.2; P = 0.004) and multivariate analysis (HR 2.3; 95% CI:1.1–4.6, P = 0.016) compared with patients without this signature. Within the group of patients with Gleason score (GS) 6 and 7 PCA, the signature added prognostic value beyond GS and identified patients at higher risk of cancer deaths more accurately than GS alone or in combination with ERG status. Protein expression of the 10 genes were significantly associated with ERG and disease progression regardless of ERG status. Conclusion: The characterized ERG‐ like signature was reflective of aggressive features of ERG ‐mediated transcription and was prognostically robust. The combination of this signature with clinicopathological variables should be validated prospectively to explore its clinical utility in stratifying patients with PCA and in identifying those at higher risk of metastatic and lethal disease.